EPortfolio as a tool for reflection and self-reflection. Issue 3 (4th May 2018) - Slepcevic-Zach, Peter; Stock, Michaela
Abstract: The request and promotion of reflection begins with an analysis of one's own understanding of education and learning as well as the connection of reflection and self-reflection and the competence development of students. A self-reflective attitude should be promoted early on by encouraging students to understand (reflection), to evaluate (evaluation), and, if necessary, to adapt (regulation) their own learning behavior. To encourage reflection, self-reflection, and competence development, the use of an ePortfolio can provide a valuable contribution. However, the implementation process of an ePortfolio for pre-service teachers remains a debated method. This research paper investigates the impact and sustainability of an ePortfolio-implementation regarding students' competence development and reflection skills in a Master's Program for Business Education and Development (BED). The survey was conducted between October 2011 and June 2014 (n = 811) and consists of six sequential questionnaires. The students assessed the positive impact on their (self-)reflection. When being asked about their most distinctive competences, students' responses emphasize their previous ePortfolio-sessions, thus indicating a positive impact of the ePortfolio on students' self-perceived competences.